Notes on Heteroscyphus (Tayl.) Schiffn.(Geocalycaceae: Jungermanniales) of the Lowland Tarai, Nepal - Pradhan, N.; Joshi, S. D. (Journal of Natural History Museum, 2009)
Heteroscyphus (Tayl.) Schiffin. of Geocalycaceae of the order Jungermannials (Hepaticae: Bryophytes) was explored entirely in the low land areas where two species were resulted, of them Heteroscyphus planus (Mitt.) Schiffn. is a new record for the country. Five species of Heteroscyphus including two lowland species are presented here. Key Words: Bryophyta; Lowland; species; New record; Jungermanniales. Journal of Natural History Museum Vol. 24, 2009 Page : 113-120